Biocatalytic asymmetric synthesis of beta-amino acids for peptidomimetics - Phathutshedzo, Masithi (My University, 2019)
There is an increasing demand for enzymes that can transform synthetic compounds with high regio-, chemo-, and enantioselectivity. Single enantiomer compounds are in high demand from the agrochemical and pharmaceutical industries for the improvement of the compound’s efficacy and reduction in side-effects. Synthesis of optically pure aromatic β-amino acids has recently attracted attention for their application in many pharmacologically active compounds. However, to date there are still no efficient synthetic methods for their preparation. Omega-transaminases (ω-TAs) are stereospecific enzymes that can either be applied for the asymmetric synthesis of β- amino acids from their corresponding ketones or kinetic resolution of racemic β-amino acids. The asymmetric synthesis is more advantageous because it leads to 100% of β- amino acid product, and is therefore a major focus of this dissertation. In previous studies, ω-transaminases could not be applied efficiently on asymmetric synthesis of enantiopure aromatic β-amino acids due to the decarboxylation of β-keto acids. In this study, we report an asymmetric synthesis strategy to circumvent the decarboxylation problem via reductive amination hydrolysis (RAH) of stable aromatic β- ketonitrile substrates. In this work, aromatic carboxylic acids were initially converted to carboxylic esters using thionyl chloride, and then subsequent nucleophilic substitution by lithiated acetonitrile resulted into aromatic β-ketonitriles. The thermodynamically stable aromatic β- ketonitriles were converted to aromatic β-aminonitriles using ω-TA in using the LDH pyruvate removal mixture as well as in the presence of the diamine donor oxylylenediamine dihydrochloride. However low yields were obtained due to sideii reactions and low enzyme activity, and therefore the subsequent steps in the project were demonstrated using commercial material. Hydrolysis of racemic aromatic β-aminonitriles into β-aminoamides as a first step towards conversion to carboxylic acids, was achieved using isolated nitrile hydratase from Rhodococcus rhodochrous ATCC BAA-870 (NHase). For determination of substrate specificity, NHase was also tested on β-ketonitrile substrates. Enantiopure aromatic β-amino acids were incorporated into wound healing peptides. The synthesis of these peptides was performed using solid phase peptide synthesis (SPPS). Successful synthesis of the wound healing peptides has been achieved, as well as their modification by attaching palmitic acid and adamantane for improving their membrane permeability. The biological activity of these peptides will be evaluated in future work.